2019
DOI: 10.4103/jfmpc.jfmpc_478_19
|View full text |Cite
|
Sign up to set email alerts
|

Causes, comorbidities and current status of chronic kidney disease: A community perspective from North Kerala

Abstract: Context:Chronic kidney disease is an upcoming public health problem characterized by premature mortality and expensive treatment in low resource settings where diabetes is highly prevalent.Aim:To find out the causes and comorbidities and to explore the community support systems for treatments availed.Settings and Design:Community based cross sectional design.Materials and Methods:Interview of known chronic kidney disease patients above 18 years registered under palliative clinics.Statistical Analysis Used:Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In our analysis, CKD a common comorbidity of diabetes [ 23 ] and hypertension [ 24 ], increased almost two times the risk of death in comparison to people without this disease. Cheng et al [ 25 ] reported that 13.1% of the people admitted to hospitalization in China had kidney failure.…”
Section: Discussionmentioning
confidence: 94%
“…In our analysis, CKD a common comorbidity of diabetes [ 23 ] and hypertension [ 24 ], increased almost two times the risk of death in comparison to people without this disease. Cheng et al [ 25 ] reported that 13.1% of the people admitted to hospitalization in China had kidney failure.…”
Section: Discussionmentioning
confidence: 94%
“…In our analysis CKD, a common comorbidity of diabetes (19) and hypertension (20), increased 1.85 times the risk of death in comparison to people without this disease. Cheng et al (21) reported that 13.1% of the people admitted to hospitalization in China had kidney failure.…”
Section: Discussionmentioning
confidence: 82%
“…Diabetes is one of the most common comorbidities in ESRD and should be considered when devising transplant treatment plans. 12,13 Diabetes was associated with postoperative urinary retention, UTI, and urosepsis. However, it did not factor into the linear regression models as significant.…”
Section: Discussionmentioning
confidence: 97%